مساهمات اللغة العربية في أسلمة وسائل الإعلام في ماليزيا: The Contributions of Arabic Language in the Islamization of Mass Media in Malaysia - Farah Ayuni Bt Mohd Husni; Rahmah Binti Ahmad H. Osman; Nurhaziqah Bt Fadzli; ‘Aqilah Bt Mohd Noor (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
مع مرور الزمن، أصبحت اللغة العربية لغة عالمية حيث كانت واحدة من خمس لغات أكثر تحدثًا في العالم. ومن بينها ماليزيا، حيث يتم تعليم وتعلم اللغة العربية على نطاق واسع في المدارس والجامعات. خاصة يمكننا أن نرى الاستخدام الواسع للغة العربية في وسائل الإعلام في ماليزيا، وغالبا ترتبط بالمحتوى الديني وخاصة المحتوى الديني الإسلامي. فتهدف هذه الدراسة إلى تسليط الضوء على مساهمات اللغة العربية في أسلمة وسائل الإعلام خاصة التلفزيون والإذاعة والصحفية في ماليزيا. وأظهرت النتائج أن اللغة العربية هي من العوامل التي تؤدي إلى أسلمة في ماليزيا بظهور كتابة جاوية واستخدام اللغة العربية في البرامج الإسلامية على التلفزيون وغير ذلك. Abstract As time passed, Arabic Language has become a worldwide language which it has become one of the five most spoken language in the world. Among them is Malaysia, where Arabic Language is widely taught in schools and universities. Especially we can see the widespread use of Arabic Language in the mass media of Malaysia and constantly relate with religious content especially Islamic content. This study’s aims are to highlight the contributions of Arabic Language in Islamization of mass media in Malaysia. In the end, the results showed that Arabic Language indeed is one of the main reasons for the islamisation in Malaysia with emergence of Javanese writing, and the use of Arabic Language on television for Islamic shows and so on.